'I Think I can': Measuring Confidence in Goal Pursuit. (February 2014) - Poulsen, Anne A; Ziviani, Jenny; Kotaniemi, Katja; Law, Mary
Client-centred occupational therapy approaches aim to increase client motivation and confidence in working towards self-identified occupational performance goals. In this opinion piece we explore whether measurement of confidence in goal pursuit could complement existing tools, such as the Canadian Occupational Performance Measure (Law et al 1998), in documenting clinical outcomes. Cognitive theories of motivation and behaviour change support links between confidence in problem solving around self-identified goals, effort, and motivation to persist and engage in therapy. We propose that evaluating goal-related confidence is an important but neglected area of practice. Providing feedback about confidence in relation to goal pursuit may increase the likelihood of occupational performance goals being attained.